Manajemen Pemerintahan Umar: Studi Dasar-dasar Pemerintahan Modern Dalam Islam - M Miftahul Ulum (Justicia Islamica, 2006)
This study aims to analyze the governance of Umar bin Khattab and its relevance to the principles of modern governance in Islam. Umar is known as a leader who implemented effective administrative, economic, and legal policies based on the principles of justice, transparency, and the welfare of the people. This study uses a qualitative method with a literature study approach, examining sources of Islamic history and modern governance literature. The results showed that Umar's administrative system included state financial governance, an independent judicial system, and the principle of openness in public policy. The concepts of leadership and bureaucracy that Umar applied are similar to the principles of good governance in modern government. This study emphasizes that Umar's model of government can be an inspiration in the development of an Islamic system of government that is adaptive and responsive to the needs of contemporary society.